2003
DOI: 10.1111/j.1600-0765.2004.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ expression of RANKL, RANK, osteoprotegerin and cytokines in osteoclasts of rat periodontal tissue

Abstract: These findings suggest that an autocrine mechanism of RANKL-RANK exists in osteoclast, which is heightened in the pathological conditions. Furthermore, the autocrine mechanism of IL-1beta and TNFalpha is also provided in osteoclast under pathological condition. These autocrine mechanisms therefore seem to regulate the osteoclast function in both physiological and pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 29 publications
3
73
0
5
Order By: Relevance
“…These results suggest that the inhibition of HIF-1 transcriptional activity and VEGF expression is also involved in antioxidant-induced retardation of orthodontic tooth movement through the down-regulation of osteoclastogenesis and subsequent bone resorption. Receptor activator of nuclear factor-κB ligand (RANKL) is an essential factor for osteoclastogenesis, and RANKL expression is up-regulated in the compression side of PDL tissues (Ogasawara et al, 2004;Wada et al, 2006). RANKL expression was also up-regulated by hypoxia in PDLFs, and antioxidants diminished hypoxia-induced RANKL expression in PDLFs in vitro and in the rat PDL tissues in vivo [data not shown, Park et al (in press)].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the inhibition of HIF-1 transcriptional activity and VEGF expression is also involved in antioxidant-induced retardation of orthodontic tooth movement through the down-regulation of osteoclastogenesis and subsequent bone resorption. Receptor activator of nuclear factor-κB ligand (RANKL) is an essential factor for osteoclastogenesis, and RANKL expression is up-regulated in the compression side of PDL tissues (Ogasawara et al, 2004;Wada et al, 2006). RANKL expression was also up-regulated by hypoxia in PDLFs, and antioxidants diminished hypoxia-induced RANKL expression in PDLFs in vitro and in the rat PDL tissues in vivo [data not shown, Park et al (in press)].…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines induce recruitment of endothelial cells (monocytes) that differentiate into osteoclasts after binding of RANKL (receptor activator of nuclear factor kappa ligand), an osteoclast differentiation factor (Ogasawara et al, 2004). On the ERR side, an animal study and one clinical association study revealed that absence or a mutant gene (less transcribed) of IL1-β are respectively linked to increase in orthodontic ERR Al-Qawasmi et al, 2003a).…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…RANKL induces osteoclast differentiation from hematopoietic precursors and stimulates the bone-resorbing activity of osteoclasts (Suda et al, 1999;Udagawa et al, 1999). It has been reported that continuous compression up-regulates RANKL expression in rat PDL in vivo (Ogasawara et al, 2004). Compressive force significantly increases the expression of RANKL but decreases osteoprotegerin, a decoy receptor for RANKL, in human PDL fibroblasts (PDLFs) cultured in vitro in a time-and magnitude-dependent manner (Nishijima et al, 2006).…”
Section: Introductionmentioning
confidence: 99%